The Effect of Endo-1,4-β-xylanase as a Feed Additive on the Growth and Overall Health of Broiler Chickens - Fadholly, Amaq; Aurellia, Sharon (IPB University, 2025)
Enzyme has been used widely as a feed additive to complement poultry needs of nutrition. Endo-1,4 beta-xylanase as its main component, which is effective in digesting non-starch polysaccharides (NSPs), hence improving the digestive system. This research aims to observe the efficacy of Endo-1,4-β-xylanase as a growth promotor and its safety. A total of 96 chickens were used in this research, divided into four groups. Administration depending on each group was conducted for 28 days, consecutively. Growth parameters that were observed includes body weight gain and feed conversion ratio, meanwhile for safety assessment, the parameters used were mortality rate, and blood profile. Based on the results, the enzyme was proven to enhance growth performance through the increased body weight gain and final weight. This is due to the enzyme’s mechanism which improves nutrient utilization. Based on the safety assessment, Endo-1,4-β-xylanase was also proven to be safe, not causing any inflammation responses in the body nor organ damage based on the blood assessment.